Intensitas Penyakit Cabai Rawit (Capsicum frutescens) di Desa Sumber Baru Kecamatan Mesuji Raya Kabupaten Ogan Komering Ilir - Nurfadhilah, Laili; Hamidson, Harman; Rahmadani, Ria; Deswita, Adelia; Randah, Nahdatul Fatiyah; Dewi, Syahrina; Mustika Sari, Sinta (Seminar Nasional Lahan Suboptimal, 2024)
Nurfadhilah, L., Hamidson, H., Rahmadani, R., Deswita, A., Fatiyah, R.N., Dewi, S., & Sari, S.M. (2024). Intensity of pest and disease attacks of cayenne pepper (Capsicum Frutescens) in Sumber Baru Village, Mesuji Raya District, Ogan Komering Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 743–752).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Cayenne pepper (Capsicum frutescens L.) is a horticultural plant that is inseparable from disease attacks caused by Plant Pest Organisms (OPT). Gemini virus is an important virus in chili plants because it is very damaging to the growth of chili plants. The aimed of this research is to determine the level of disease attack on cayenne pepper plants in Sumber Baru Village, Mesuji Raya District, Ogan Komering Ilir Regency. The method used is the case study method and data collection using the census method by observing the level of disease attacks in cayenne pepper attacks. The results of research conducted in Sumber Baru Village, Mesuji Raya District, Ogan Komering Ilir Regency show that there are four diseases that attack cayenne pepper plants, namely gemini virus, Choanephora rot, leaf spot, and sclerotium wilt. It is known that the highest percentage of disease attacks was Gemini virus disease with an average of 97.05% and the highest percentage in the sixth observation was 97.9%, this shows that almost all plants were attacked by Gemini virus which was caused by the vector, namely the whitefly. Several disease symptoms were found on cayenne pepper plants, namely anthracnose which appeared on the fruit which started with brown spots, then spread and rotted, leaf spot which caused brown spots on cayenne pepper leaves, then rot on the stems, the symptoms were rotten stems and brown color, and fruit rot, the fruit becomes rotten and smells bad. The highest percentage of attacks was Gemini virus attack at 97.05% and Choanephora rot at 57.33%. It is known that the highest intensity of disease attack is Gemini virus disease which is caused by vectors, namely whitefly and fruit rot caused by Choanephora cucurbitarum with a very heavy level of attack.